What are the implications for patient safety and experience of a major healthcare IT breakdown? A qualitative study - Scantlebury, Arabella (Digit Health, 2021)
INTRODUCTION: To explore the impact of a three-week downtime to an electronic pathology system on patient safety and experience. METHODS: Qualitative study consisting of semi-structured interviews and a focus group at a large NHS teaching hospital in England. Participants included NHS staff (n = 16) who represented a variety of staff groups (doctors, nurses, healthcare assistants) and board members. Data were collected 2–5 months after the outage and were analysed thematically. RESULTS: We present the implications which the IT breakdown had for both patient safety and patient experience. Whilst there was no actual recorded harm to patients during the crisis, there was strong and divided opinion regarding the potential for a major safety incident to have occurred. Formal guidance existed to assist staff to navigate the outage but there was predominantly a reliance on informal workarounds. Junior clinicians seemed to struggle without access to routine blood test results whilst senior clinicians seemed largely unperturbed. Patient experience was negatively affected due to the extensive wait time for manually processed diagnostic tests, increasing logistical problems for patients. CONCLUSION: The potential negative consequences on patient safety and experience relating to IT failures cannot be underestimated. To minimise risks during times of crisis, clear communication involving all relevant stakeholders, and guidance and management strategies that are agreed upon and communicated to all staff are recommended. To improve patient experience flexible approaches to patient management are suggested.